The addition of sugarcane bagasse and asparagus peel enhances the properties of sweet potato starch foams - Cruz-Tirado, J.P. (2019)
ABSTRACT The agro-industrial wastes, sugarcane bagasse (SB) and asparagus peel (AP), were used to enhance the properties of biodegradable foam trays based on sweet potato starch-based foam trays (starch/SB and starch/AP trays, respectively). Starch/SB and starch/AP trays containing different concentrations of SB and AP (0%-40%, w/w) were prepared, and their microstructure and physical, thermal, and mechanical properties were characterized. The addition of fibers wastes allowed obtaining a yellowish foam tray with lower luminosity and higher porosity, mechanical resistance, deformability, and better ability to absorb water as compared with the sweet potato starch foam trays without fibers. The addition of SB yielded foam trays less porous, with lower water absorption capacity and greater tensile strength than the addition of AP. Higher concentrations of AP fibers (greater than 30%) generate more extendible foam trays. The addition of fibrous wastes improved the thermal stability of the sweet potato starch foam trays. The composite foam trays produced in this work could be used as substitutes for expanded polystyrene in dry food packaging.